The Effect of Tax Literacy, Taxpayer Awareness, and Tax Sanctions on MSME Tax Compliance - Erina Dwiyanti; Made Aristia Prayudi; Ni Kadek Sinarwati (Universitas Muhammadiyah Makassar, 2026)
MSMEs play an important role in supporting economic growth and increasing state revenue through taxation. However, the level of tax compliance among MSME taxpayers in Indonesia remains relatively low. This study aims to examine the effect of tax literacy, taxpayer awareness, and tax sanctions on MSME tax compliance in Denpasar. The study applies a quantitative approach using primary data collected through questionnaires distributed to MSME taxpayers. The sampling technique used purposive sampling, resulting in 150 respondents who met the research criteria. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, classical assumption tests were carried out, including normality, multicollinearity, and heteroscedasticity tests, and the results indicated that the regression model fulfilled the required assumptions. The findings reveal that tax literacy has a positive and significant effect on MSME tax compliance. Taxpayer awareness also positively and significantly affects MSME tax compliance. In addition, tax sanctions were found to have a positive and significant effect on taxpayer compliance. Simultaneously, tax literacy, taxpayer awareness, and tax sanctions significantly influence MSME tax compliance. The coefficient of determination shows that 54.1% of the variation in MSME tax compliance can be explained by the independent variables. These findings imply that improving tax education, strengthening taxpayer awareness, and implementing consistent tax sanctions can enhance voluntary tax compliance among MSMEs.